Touraine-Solente-Gole Syndrome: A Rare Case Report - Dharmil Doshi; Dipali Satani; Shwetambari Singh (Delhi Journal of Ophthalmology)
Touraine-Solente-Gole Syndrome, also known as Pachydermoperiostosis (PDP) or Primary Hypertrophic Osteoarthropathy, is a rare hereditary disorder, which affects both bones and skin. It is characterized by a combination of dermatologic changes (pachydermia or thickening of the skin) and rheumatologic manifestations (periostosis and finger clubbing). Eyelid ptosis which is caused by thickened eyelids (blepharoptosis) is a less common symptom. We report the case of a patient with a complete form of Touraine-Solente-Gole Syndrome with bilateral blepharoptosis as presenting feature.